The Polar Eskimos - Wright, John (Polar Record, 1939)
We read and hear so often of the harm done to primitive peoples by contact with European culture, that it is refreshing to find an exception to this rule. The Polar Eskimos of North-West Greenland were introduced to European culture through the visits of expeditions to that region, and there was no control of these until thirty years ago. Yet these Eskimos do not seem to have suffered any harm or to have lost their original independence. A journey to West Greenland is apt to be disappointing, because the original Eskimo race and culture has been greatly modified, but to visit Thule is to see the Eskimos of the story books, dressed in furs and eating literally almost nothing but meat and blubber, most of it raw.